Dô. Vī. Rāghavan smrtigranthaḥ - Raghavan, V.; Subrahmaṇyam Śāstrī, Vī., 1907- (Caukhambhā prācyavidyā granthamālā ;, 1983)
Comprises articles on Sanskrit studies and on the life and works of V. Raghavan, 1908-1979, Sanskritist.